Early bile drainage improves native liver survival in biliary atresia without cholangitis - Liu, Fei; Xu, Xiaogang; Liang, Zijian; Tao, Boyuan; Lan, Menglong; Zeng, Jixiao (Frontiers in Pediatrics, 2023)
[OBJECTIVES] To explore the outcomes and related factors in children without cholangitis after Kasai portoenterostomy (KPE). [METHODS] We retrospectively analyzed the data of infants with type III BA who underwent KPE from June 2016 to December 2021. We compared and analyzed the difference in native liver survival (NLS) rates in different types of cholangitis. We also investigated the relationship between the absence of cholangitis and the effect of early bile drainage (EBD) as well as the related factors affecting EBD efficacy. [RESULTS] A total of 145 children were included in this study. Among these children, 82 (56.6%, 82/145) had cholangitis, including 40 (48.8%, 40/82) with early cholangitis and 33 (40.2%, 33/82) with recurrent cholangitis. The median follow-up period was 29 months (range, 2-75 months). The NLS rates were 67.6%, 51.7%, 45.5% and 43.4% at 6 months, 1 year, 2 years and 5 years following KPE, while the NLS rates for infants without cholangitis after KPE were 68.3%, 50.8%, 46.0% and 46.0%, respectively. Higher gamma-glutamyl transferase (γ- GT) and total bile acid (TBA) before KPE were risk factors for cholangitis (P<0.05). The NLS rate in recurrent cholangitis was significantly lower than that in occasional cholangitis (P<0.01). Compared with the EBD-poor group, the NLS rate in the EBD-good group of infants was significantly increased (P<0.001). EBD was significantly correlated with the occurrence and frequency of cholangitis (P<0.05). [CONCLUSIONS] Recurrent cholangitis was an important factor affecting NLS. For children without cholangitis after KPE, early bile drainage was better, and the NLS was longer.